Pengembangan Aplikasi Pembelajaran Sistem Informasi Sekolah berbasis Web menggunakan Metode Extreme Programming (Studi Kasus: Al-Izzah International Islamic Boarding School Kota Batu) - Zainal Abidin; Buce Trias Hanggara; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Al-Izzah International Islamic Boarding School, Batu City, is a school that connects the basic values ​​of Islam with comprehensive knowledge of these rapidly changing times. The process of teaching and learning activities is carried out as a whole, which collects the development and general knowledge of students' Islamic values. The process of teaching and learning activities must be carried out face-to-face in the classroom, when teachers cannot participate in learning activities in class, the delivery of material is naturally hampered. This problem resulted in student learning not optimal, besides that the teacher also had to catch up on the material that was left behind. To help teachers and students in the teaching process, implement learning applications on browser devices so that they can be accessed anytime, anywhere. This application has a function to study the existing material, do assignments and evaluate. The application was developed using the extreme programming method which resulted in three iterations. Extreme programming is a method that focuses on faster results. In addition, this method is suitable for users with unclear and changing needs. According to the needs analysis, 26 functional requirements were generated. According to the test results, it is declared valid which means the application can run well. The results of user acceptance testing, learning applications get an assessment from users, namely with a percentage of 81.47%. It can be concluded from these results that the application is declared approved or accepted by the user.